The Rhetorical Analysis of The Eschatology In Surah Al-Baqarah Based On Semantics - Bushro Bakri; Khairul Asyraf Mohd Nathir; Rosni Samah; Amani Nawi; Mohd Adi Amzar Muhammad Nawawi; Mohamad Yazid Abdul Majid (Ijaz Arabi Journal of Arabic Learning, 2026)
Ilm Ma`ani (semantics) holds significant importance in understanding the miraculous of the Qur'an, as it focuses on studying words, sentences, their meanings, and how they interact with context and the speaker's intent. A failure to apply these Ilm Ma`ani (semantics) may lead to a misunderstanding of the speaker's intended purpose. Therefore, this research aims to analyze the intended meaning of the verses that contain the word (Al-Qiyamah) in Surah Al-Baqarah to obtain a concept of admonition and warning. This methode for this study is content analysis method, where the researchers analyzed the Qur'anic verses in Surah Al-Baqarah that contain the word (Al-Qiyamah). The researchers found four verses in Surah Al-Baqarah that contain the word (Al-Qiyamah). The results from the semantic analysis showed that all the topics of Ilm Ma`ani (semantics), which carry rhetorical purposes according to the context, are provided. These rhetorical purposes lead to a sense of admonition and warning in preparation for the Day of Resurrection. The topics of the Ilm Ma'ani include declarative style (khabar), interrogative style (insha'), subject (musnad), predicate (musnad ilayh), exclusivity style (qasr), conjunction and separation style (fasl wa wasl), balance, brevity, and verbosity (musaawat, ijaz, and itnab), and verb-related elements (muta'allaqat al-fi'l). The rhetorical purposes derived from these analyses are reproach and disapproval, reflection and contemplation, warning, emphasizing God's judgment, highlighting contradictions, threat, emphasizing recompense, encouraging repentance, warning and guidance, and emphasizing God's power and many more depending on the context of the verses.